2020
DOI: 10.3389/fpls.2020.00683
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationships of Wood Anatomical Traits in Norway Spruce

Abstract: The quantitative assessment of wood anatomical traits offers important insights into those factors that shape tree growth. While it is known that conduit diameter, cell wall thickness, and wood density vary substantially between and within species, the interconnection between wood anatomical traits, tree-ring width, tree height and age, as well as environment effects on wood anatomy remain unclear. Here, we measure and derived 65 wood anatomical traits in cross-sections of the five outermost tree rings (2008-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…This study has shown that the emerging field of quantitative wood anatomy complements both dendroecological studies and climate change research (Buttò et al, 2020;Piermattei et al, 2020). For example, vessel area and distribution, in addition to annual tree ring width, provide a better understanding of how changes in growing conditions affect not only radial growth, but also wood anatomy and its properties.…”
Section: Discussionmentioning
confidence: 89%
“…This study has shown that the emerging field of quantitative wood anatomy complements both dendroecological studies and climate change research (Buttò et al, 2020;Piermattei et al, 2020). For example, vessel area and distribution, in addition to annual tree ring width, provide a better understanding of how changes in growing conditions affect not only radial growth, but also wood anatomy and its properties.…”
Section: Discussionmentioning
confidence: 89%
“…One study reported marginal differences in intercept ( P = 0.02) between Fraxinus trees growing in soils with high vs low moisture retention (Kiorapostolou & Petit, 2019). In temperate conifers, various researchers have found constant tip‐to‐base conduit widening across gradients of nutrient availability and temperature (Coomes et al ., 2007; Piermattei et al ., 2020), and even across trees subject to experimental manipulation of CO 2 concentration and soil temperature (Prendin et al ., 2018b). Similarly, water availability did not affect the slope or the intercept of the relationship between mean vessel diameter per species and stem length across hundreds of angiosperm species spanning most of the world’s climates (Olson et al ., 2014, 2018b; Morris et al ., 2018).…”
Section: Conduit Widening Is Unlikely To Be Nonadaptivementioning
confidence: 99%
“…Sampling with respect to distance from the ground (Li et al ., 2019) will not standardize measurements because widening begins at the stem tip and proceeds through the base into the roots, making distance from the base an arbitrary reference point (Box 2; Prendin et al ., 2018b). Even what index of conduit diameter best reflects selection acting on plant hydraulics is an object for research; in Picea abies , there is evidence that tangential diameter provides better biological signal than radial diameter (Rosner et al ., 2016; Piermattei et al ., 2020). Similarly, given that species differ in how direct or circuitous the route is that water takes within stems (Vité & Rudinsky, 1959; Waisel et al ., 1972), even how to measure path length precisely requires examination.…”
Section: A Change In the Plant Hydraulics Paradigm: From Cross‐sectiomentioning
confidence: 99%
“…Developing such programs may strengthen and diversify proxies by considering NC, LD, and other dendroanatomical and QWA parameters that could be integrated well with dendrochronology. It contributes toward more fully understanding the sensitivity of trees to climate ( Olano et al, 2012 ; Piermattei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the Tropics, where the instrumental climate record is inadequate, dendroclimatology is limited to annual or seasonal resolution ( Worbes, 2002 ; Mokria et al, 2017 ; Gebregeorgis et al, 2020 ). However, finer temporal resolutions could be attained by extracting environmental information recorded in the dimensions of conifer wood cells, as it has been done for temperate and Mediterranean regions ( Panyushkina et al, 2003 ; Liang et al, 2013 ; Hetzer et al, 2014 ; Castagneri et al, 2018 ; Piermattei et al, 2020 ). Dendroanatomy and quantitative wood anatomy (QWA) are fields of study aiming to support long-term intra-annual dendroclimatology ( Panyushkina et al, 2003 ; Olano et al, 2012 ; Liang et al, 2013 ; Björklund et al, 2020 ; Lange et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%